Production of Tsr factor by Rhizobium meliloti - Jain, V; Garg, N; Nainawatee, H S (Folia microbiologica, 1991)
The root exudates of alfalfa (Medicago sativa) and mungbean (Vigna radiata) induced the Tsr (thick and short roots) factor production in Rhizobium meliloti. The factor caused a 30-40% reduction of root length in alfalfa seedlings. Pea root exudate had no Tsr induction activity. The flavonoid naringenin could replace the roots in inducing Tsr production. Naringenin-induced Tsr factor caused 70% shortening of main roots. The Tsr inducing property of naringenin was specific since quercetin and syringaldehyde had no such effect.
Keywords: flavonoidy; Flavonoids; Flavanones; flavanony; Bacterial Proteins; membránové proteiny; Membrane Proteins; Sinorhizobium meliloti; Medicago sativa; bakteriální proteiny